Clinical and Histological Findings of Denture Stomatitis as Related to Intraoral Colonization Patterns of Candida albicans, Salivary Flow, and Dry Mouth. Issue 1 (25th October 2012) - Altarawneh, Sandra; Bencharit, Sompop; Mendoza, Luisito; Curran, Alice; Barrow, David; Barros, Silvana; Preisser, John; Loewy, Zvi G.; Gendreau, Linda; Offenbacher, Steven
Abstract Purpose: Multifactorial etiological factors contribute to denture stomatitis (DS), a type of oral candidiasis; however, unlike other oral candidiasis, DS can occur in a healthy person wearing a denture. In this study, we therefore attempt to explore the association between candida, denture, and mucosal tissue using (1) exfoliative cytology, (2) the candidal levels present in saliva, on mucosal tissues and on denture surfaces, and (3) the salivary flow rate and xerostomic symptoms. Materials and Methods: A cross‐sectional study enrolled 32 edentulous participants, 17 without DS as controls and 15 with DS (Newton's classification type II and III). Participants with systemic or other known oral conditions were excluded. Participants completed a xerostomia questionnaire, and salivary flow rates were measured. Samples of unstimulated whole saliva (UWS) and stimulated whole saliva (SWS) were collected. UWS was used for fungal culturing. Periodic acid‐Schiff (PAS) stain and quantitative exfoliative cytology were performed on samples from affected and unaffected mucosa from each participant. Levels of Candida species (albicans and non‐albicans) were determined in salivary samples (expressed as colony‐forming units, CFU), as well as from swab samples obtained from denture fitting surfaces, in addition to affected and unaffected mucosa. Results: There were no significant differences in salivary flow rates, mucosal wetness, or frequency of reported dry mouth comparing participants with and without DS. Exfoliative cytology of mucosal smears demonstrated significantly higher (p= 0.02) inflammatory cell counts in DS patients, as compared with smears of healthy denture‐wearers. Candida albicans was significantly more prevalent in saliva (p= 0.03) and on denture surfaces (p= 0.002) of DS participants, whereas mucosal candidal counts and the presence of cytological hyphae did not show significant difference comparing DS to healthy participants. Conclusions: In this investigation, we presented a unique group of healthy edentulous patients. This population may reflect the general DS population without systemic or other oral diseases. The prominent etiological factor for DS in this population is the presence of candida in denture and saliva. We found that other factors such as saliva flow/xerostomia, fitting of the denture, and the presence of candida in the mucosa, are less important in this population. Therefore, DS treatments in healthy patients should first focus on sanitization of an existing denture and/or fabrication of a new denture.